Continuous usage intention of e-wallet during the Covid-19 pandemic: A Malaysian Case - Yapp, Emily Hon Tshin; Noratikah Husna; Jasmine A.L. Yeap (Universal Publishers, 2022)
The goal of this research is to discover characteristics that influence Malaysians' continued usage intention to use e-wallets as a payment mechanism during the Covid-19 pandemic. Design/methodology/approach: Purposive sampling was utilized to obtain data from 417 Malaysians via a self-administered online questionnaire. SPSS version 26 and SmartPLS 3.3.3 were used to analyse the data. Enjoyment, incentive, convenience, and habit contribute positively towards users’ continuous usage intention on e-wallets. On the other hand, incentive and convenience have a high influence on users' continuing usage of e-wallets, but pleasure and habit have a modest effect. However, the analysis results demonstrate that subjective norm was not significant in determining users' continuous usage intention. The data was collected in Malaysia during the Covid-19 Pandemic. Therefore, the results of this research cannot be generalised to other counties. E-wallet services providers should pay attention particularly users enjoyment, incentive, convenience and habit because these factor will contribute to users’ continuous usage intention on e-wallets. OThis research provides understanding on what are the essential elements of users’ continuous usage intention on e-wallet among the Malaysian during the Covid-19 pandemic. Although past researchers had studied about enjoyment, subjective norms, and habit as the essential elements of users’ continuous usage intention on e-wallet, however health risk, incentive and convenience are other essential elements that are being added into the study. Certainly, these essentials elements needed attention particularly during the Covid-19 pandemic.